PHARMACOLOGICAL ANALYSIS OF OBNOXIOUS WATER WEED: EICHHORNIA CRASSIPES (MART.) SOLMS - S. Khalid; 2; S. Shaheen; K. Hussain; M. N. Shahid; S. Sarwar1. (Journal of Animal and Plant Sciences, 2020)
Eichhornia crassipes (Mart.) Solms, commonly known as water hyacinth, an aquatic plant coined to diverse activities including its role as an obnoxious weed with tremendous economic and aesthetic implications. The aim of the current experiment was to explore antimicrobial, antioxidant and phytochemical properties of this weed while using different non-polar solvents viz., petroleum ether, chloroform and polar solvents i.e., methanol and aqueous (distilled water) solvent extracts of root, stem and leaf of E. crassipes. Disc diffusion method was employed to analyse the antifungal activity against two fungi (Penicillium italicum and Botrytis cinerea) and antibacterial activities against two bacteria viz. Xanthomonas axonopodis and Bordetella pertussis. The extracts of weed showed significant activity against these two fungi and two bacteria when compared to standard. Maximum antifungal and antibacterial potential was recorded in leaf chloroform extract against B. cinerea (29 mm) and in leaf methanol extract against B. pertussis (17 mm) respectively among other extracts. Moreover, antioxidant potential of weed also showed the presence of significant secondary metabolites. Phytochemical analysis indicate presence of alkaloids, coumarins, terpenoids, tannins and flavonoides and absence of saponins, anthrax-quinones, phlobatanins and cardiac glycosides by standard procedures. These results also depict the significance of the plant in pharmaceutical industry.
Keywords: Eichhornia crassipes; antibacterial activity; antioxidant activity; phytochemical analysis